Noise Level Estimation in the Shortwave Frequency Range - Lossmann, E.; Meister, M. A.; Madar, U. (Elektronika ir Elektrotechnika, 2011)
Noise is a composite signal by nature, changing widely over time, and some of its components can be controlled while the others cannot. Although the signal-to-noise ratio (SNR) is the main factor determining the signal quality at the receiving end, it is quite complicated to define the characteristics of the local noise, especially in the shortwave bands. This paper provides an overview of the background noise measurements to evaluate the problematic shortwave communications sites in Estonia and to assess their suitability as radio receiving sites. Extensive statistical data was collected during the study, the sources of interference were identified and their spatiotemporal influence was analyzed. Monitoring results were compared to methods and models, presented in recommendation ITU-R P.372-9. Ill. 9, bibl. 7, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.454